Polıcy Analysıs Of Forest And Land Rehabılıtatıon (RHL) At The Krueng Aceh Protected Forest Watershed Management Center (BPDASHL) In Central Aceh Dıstrıct, Aceh Provınce - Rivai Ahmad; V Rudy Handoko; Bambang Kusbandrijo (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The issue of forest destruction by communities and companies in Indonesia has received attention from various countries, and has become an international issue. This study aims to describe and identify the obstacles to the implementation of the Forest and Land Rehabilitation Program Policy which involves many elements in society in Central Aceh District. This descriptive qualitative research uses a data triangulation analysis approach, taking document data and interviews which are confirmed by data from reports from forest monitoring NGOs in Central Aceh District. The results of the study found that the forest conservation policies supported by regional regulations in the form of the Aceh Qanun had not been implemented as stipulated due to constraints on the number of human resources and the budget and competence of human resources. The construction of the proposed implementation model is to involve the community by optimizing community forest protection organizations (PHBM) combined with an economic approach as a form of mutualist relations with the target of increasing community participation and responsibility